Leadership Through the Lens of Gender Norms and Identities - Maryam; Muhammad Idris; Abdul Ghaffar (Journal of Management Practices, Humanities and Social Sciences, 2022)
Gender norms and identities play a significant role in either supporting or demotivating the leadership development of individuals in their careers. Even in this era of globalization and development, the contemporary world is experiencing communities and societies where gender stereotypes are deep-rooted. In one way or another, this hinders women from equally participating with their male counterparts. Such role expectations and profiling ultimately compel women to divert their focus from leadership development toward domestic affairs. In addition, women are considered perfect for house chores rather than leadership careers. This perception also affects women very negatively in developing their careers as leaders. This study considers the barriers women face during their careers while being in a leading position in their organizations. A narrative inquiry is conducted from the female school principals at the secondary level in Khyber Pakhtunkhwa. Gender discrimination, lack of proper mentorship, and old boys’ network are the main barriers women principals face in working in a leading position in their schools. The study suggests that strong academic credentials, professional development, restructuring the organizational practices, and providing more opportunities to women can decrease gender bias.